EFFECT OF SOME BOTANICALS ON BIOLOGICAL PARAMETERS OF PULSE BEETLE (CALLOSOBRUCHUS CHINENSIS L.) IN PEA (PISUM SATIVUM L.) - MAJI, TARAK BRAMBHA; S. PAL; H. CHATTERJEE (The Bioscan, 2014)
Six ethanolic extracts viz. neem leaf, rhizome of ginger, garlic and turmeric, eucalyptus leaf and leaf of Lantana camera were evaluated to find out their effect on biological parameters of pulse beetle (Callosobruchus chinensis L.) in pea during 2009-2010. It was observed that all the botanicals were superior over control to suppress some biological parameters such as egg laid/seed, egg laid/day, oviposition period, hatchability per cent, adult formation and adult survivorship while prolonged some developmental stage such as incubation period and larval-pupal period. Among the botanicals, garlic was found to be very effective against larval development of pulse beetle thereby no adult emergence (0.00%) followed by neem and turmeric with 4.76 and 6.67% adult emergence, respectively.